Mucinous Adenocarcinoma of Gall Bladder- A Rare Histopathological Variant Presented as Perforation - Sunil Vitthalrao Jagtap (Journal of Clinical and Diagnostic Research, 2019)
Mucinous adenocarcinoma of gall bladder is a malignant tumour which is a very rare histopathological variant. We report a case of an 80-year-old female presented with pain in abdomen since 3 days with increasing severity and nausea since 1 day. On ultrasonography, area of altered echotexture in caudate lobe of liver was noted. Acute calculus perforated cholecystitis type II with associated peri-gall bladder collection; abscess and peri-gall bladder inflammatory changes were noted. Sub-total cholecystectomy was performed which showed perforated gall bladder with mass lesion and on histopathology, reported as mucinous adenocarcinoma of gall bladder. We are presenting this case for its rarity and clinical, radiological and histopathological findings.